The Effect of Eucheuma cottonii Extract on Body Weight and Blood Sugar Levels of Mouse (Mus musculus) Diabetes Mellitus Type 1 - Abdu Mahid Ukratalo; Pieter Kakisina; Meigy N Mailoa (Jurnal Biologi Tropis, 2023)
Seaweed (E. cottonii) is a type of seaweed from the Rhodophyta class which has anti-diabetic activity so that it can control diabetes mellitus. The purpose of this study was to determine the effect of E. cottonii extract on body weight and blood sugar levels in mice (Mus musculus) type 1 diabetes mellitus. This study used a completely randomized factorial design with five treatments and three replications. 20 mice were divided into 5 groups: normal mice (KN), negative control (K-), positive control (K+), E. cottonii extract dose of 0.4 ml/g BW (P1) and E. cottonii extract dose of 0 .7 ml/gBB (P2). The extraction of E. cottonii used the maceration method with 96% ethanol solvent. All groups of mice were induced with 0.3 ml of STZ for 3 consecutive days. After an increase in blood glucose levels, the mice in the K(+) group were given metformin at a dose of 0.4 ml, P1 was given E. cottonii ethanol extract at a dose of 0.4 ml/g BW and P2 at a dose of 0.7 ml/g BW. Extract administration was carried out for 7 days. The results showed that E. cottonii extract had an effect on increasing body weight and decreasing blood sugar levels in type 1 diabetes mellitus mice. The increase in body weight and decrease in blood sugar levels was in line with the high doses given.